Predictors of Mortality in Methanol Poisoning: A Systematic Review and Meta-analysis - Gheshlaghi, Farzad; Rezaei, Mohammad Reza; Eizadi-Mood, Nastaran; Fattahi, Farinaz; Nazarianpirdosti, Mohammad; Ghasemi Oskui, Aisan (International Journal of Medical Toxicology and Forensic Medicine, 2024)
Background: Today, methanol intoxication is increasing. Identifying mortality predictors has a significant correlation with poisoning progress. This meta-analysis study aimed to identify and evaluate mortality predictors for methanol poisoning. Methods: In this study, we searched electronic databases for case-control and cohort studies related to methanol poisoning. The quality of the studies was evaluated using the STROBE checklist. Comprehensive meta-analysis 3 was used to calculate the odds ratio (OR) and 95% CI of the factors present, as well as to perform heterogeneity, sensitivity, and publication bias assessments. Results: In this meta-analysis study, 14 out of 945 initial studies were included. The results identified 15 mortality predictors of methanol poisoning. The risk factors were ranked by the integrated OR values and included venous blood pH (OR=3.79, 95% CI, 2.42%, 5.19%), methanol concentration (OR=1.64, 95% CI, 1.05%, 2.55%), venous carbon dioxide pressure (PCO2) (OR=9.993, 95% CI, 5.80%, 17.18%), base deficit (OR=2.943, 95% CI, 1.20%, 7.165%), hemodialysis time (OR=2.69, 95% CI, 1.35%, 5.35%), blood sugar (OR=9.84, 95% CI=3.86, 25.09), venous bicarbonate (HCO3) (OR=2.97, 95% CI, 1.68%, 5.26%), creatinine (OR=13.10, 95% CI, 2.68%, 64.04%), potassium (K) (OR=3.51, 95% CI, 1.66%, 7.43%), alanine aminotransferase (OR=7.57, 95% CI, 1.03%, 55.57%), sodium (OR=6.69, 95% CI, 1.78%, 25.12%), white blood cells (OR=7.16, 95% CI, 1.42%, 36.16%), coma (OR=32.73, 95% CI, 18.59%, 56.70%), visual disturbances (OR=3.37, 95% CI, 1.59%, 7.16%), and gastrointestinal symptoms (OR=1.94, 95% CI, 1.16%, 3.22%). Conclusion: Identifying mortality predictors and disease progression in methanol intoxication patients can help doctors diagnose patients at risk better and faster to provide effective treatment interventions for them.